SYMBOLIC SPEECH AND RITUAL DISCOURSE: A DISCOURSE ANALYSIS OF SHAMANIC AUTHORITY IN THE PACU JALUR TRADITION OF KUANTAN SINGINGI - Albetro, Albetro; Zulfa, Zulfa; Nazmi, Ranti; Kaksim, Kaksim; Meldawati, Meldawati; Yasin, Faisal; Jamurin, Jamurin (ppjbsip, 2026)
This paper explores the role and identity of the Jalur Shaman within the Pacu Jalur rowing tradition inKuantan Singingi Regency, Indonesia. While the original approach adopts a historical-biographicalmethod, this revision reframes the study through a discourse-analytic lens to better interrogate how theshaman’s role, ritual language, and spiritual objects function as symbolic practices. The central figure,Jasri, a renowned shaman, guides the spiritual preparation of rowing teams through ritual prayers,protective symbols, and oral transmission of traditional values. Drawing from interviews and culturalobservation, the study investigates how speech, artifacts, and biography co-construct the Jalur Shaman'slegitimacy. Adopting theoretical insights from Critical Discourse Analysis and Ritual Theory, the studyanalyzes prayers as performative speech acts and the shaman’s tools (e.g., knives, necklaces) as culturaltexts encoding meanings of defense, identity, and cosmological belief. The article reveals how theauthority of a shaman is not inherited, but constructed through community narratives, ritualperformance, and symbolic alignment with ancestral power. Findings suggest that the shaman’s discoursesustains a sacred space where tradition is enacted, remembered, and renewed. Beyond preservingheritage, Jasri’s role reflects resistance against modern secularization and provides a platform forcollective spiritual identity in the postcolonial context. The study recommends incorporating discourse-sensitive approaches to analyze spiritual roles in Indigenous communities and preserving oral texts as partof intangible cultural heritage. Future research could explore the tension between institutional religiousframeworks and localized spiritual discourse in similar traditions across Southeast Asia.